Expansão urbana e variações mesoclimáticas em João Pessoa-PB - Sobreira, Liése Carneiro (2010)
The study on the relationship of urban growth with the local climate has resulted in the establishment of invariably negative phenomena, as the "heat island" and other climate variations. These findings have served as a warning to the need for changes in the current use and growth of the urban space. The city of João Pessoa, 7 ° 5‟ S latitude and 34 ° 50 ' W longitude, has presented in recent years a strong horizontal and vertical urban growth. The city has some environmentally positive features such as proximity to the sea and the existence of green areas in the central area, which can help to reduce the impact of urban growth on local climate. But still, there is the question about the impact of the urban growth on the local climate in recent years. In this context, the objective of this work is to verify if there were significant climate changes that may be correlated with urban growth in the city of João Pessoa, in the decades from 1980 to 2000. The observed variables for the characterization of urban growth are: the area of urban sprawl and quantitative data of the resident population. The observed climatic variables are rainfall and air temperature. Climatic data are from three weather stations: Station Castro Pinto Airport - location with less intense urban occupation - Station Solar Energy Laboratory UFPB - Federal University of Paraiba, located on the campus I of the university, and station National Institute of Meteorology located in the conurbation between the municipalities of João Pessoa and Cabedelo, both located at locations of major urban occupation. The results of the processing and analysis of data indicates that the air temperature of the city increased over the past 26 years, which can be correlated with the expansion of urban sprawl. It also notes that the air temperature increased more significant in the months of the warmest quarter. The findings indicate that although the environment of João Pessoa has favorable characteristic, yet the process of urbanization and densification has caused changes in the climate system of the city. There were not found considerable variations in rainfall. However, it was featured that the months that recorded more intense accumulated precipitation were preceded by a year or period of high temperature, which may indicate that there is a correlation between these phenomena.